Proceedings of the 24th International Conference on Intelligent User Interfaces 2019
DOI: 10.1145/3301275.3302322
|View full text |Cite
|
Sign up to set email alerts
|

Progressive disclosure

Abstract: As we increasingly delegate important decisions to intelligent systems, it is essential that users understand how algorithmic decisions are made. Prior work has often taken a technocentric approach to transparency. In contrast, we explore empirical user-centric methods to better understand user reactions to transparent systems. We assess user reactions to transparency in two studies. In Study 1, users anticipated that a more transparent system would perform better, but retracted this evaluation after experienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(31 citation statements)
references
References 72 publications
0
17
0
Order By: Relevance
“…Moreover, half of them were shown detailed information about the classi cation scores produced by the CNN. Our results indicate that when saliency maps were available, participants answered correctly more frequently than when they were absent (60.7% vs. 55.1%, p = 0.045). However, the overall performance was generally low even with the presence of saliency maps.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…Moreover, half of them were shown detailed information about the classi cation scores produced by the CNN. Our results indicate that when saliency maps were available, participants answered correctly more frequently than when they were absent (60.7% vs. 55.1%, p = 0.045). However, the overall performance was generally low even with the presence of saliency maps.…”
Section: Introductionmentioning
confidence: 68%
“…ey found that this helped participants to decide faster on whether to trust the prediction. Springer and Whi aker [55] conducted two user studies. ey used a system that predicted the emotional valence of participant's wri en experiences.…”
Section: Evaluations Of Saliency Map For Text Based Classi Ersmentioning
confidence: 99%
“…Since personas were first introduced, a range of other online analytics platforms, services, and tools have emerged (Cooper, 2004;Springer & Whittaker, 2019) -including Adobe Analytics, IBM Analytics, Facebook Insights, Google Analytics-as well as integrating services (e.g., HootSuite, Tableau, etc.) that organizations can use to understand their users and user segments.…”
Section: Personas and Analytics: Enemies Or Complements?mentioning
confidence: 99%
“…Transparency can increase operator trust and use of the system Springer & Whittaker, 2019). Providing the logic behind system recommendations can increase trust more than providing probabilistic assessments of risk or no explanation at all .…”
Section: Introductionmentioning
confidence: 99%
“…Providing the logic behind system recommendations can increase trust more than providing probabilistic assessments of risk or no explanation at all . However, the overall body of research is not clear in how best to design transparent systems (Springer & Whittaker, 2019).…”
Section: Introductionmentioning
confidence: 99%